Potensi Peningkatan Luas Panen, Produksi, Dan Produktivitas Kedelai Di Jawa Barat - Juri Juswadi; Pandu Sumarna; Neneng Sri Mulyati (Paspalum: Jurnal Ilmiah Pertanian, 2021)
This study aims to identify the development of harvest area, production, and productivity of West Java soybeans during the period 2004-2005, the effect of harvest area on soybean production and grouping districts in West Java based on harvest area and soybean productivity. The analytical tools used are descriptive statistics, regression analysis, and quadrant analysis. The results showed that the harvest area, production and productivity of West Java soybeans during the period 2004-2015 increase with fluctuating growth. Soybean harvest area has a very significant effect on soybean production. The results of quadrant analysis show that only Garut and Indramayu districts are in quadrant II, which have high harvest areas and soybean productivity. Bogor and Bekasi districts are in quadrant IV which have very low harvest area and soybean productivity, while the other 14 districts are in quadrant I with high soybean productivity but low harvest area.